The fiscal accusation and the preliminary hearing - Valdivia Sorrentino, Gino M. (2008)
With the insertion of the new accusatory model in the penal procedural legislation, the State Attorney' s General Office continues being the authorized one to exert the accusatory function and in merit to it to make decisions that will determine the development of the process. Legal figures such as the probatory conventions have been included to enter into agreements with the imputed and eliminate the probatory activity, which will contribute to the speed of the process and the diminution of the number of cases. This way, and under the disposition of the New Criminal Procedural Code, a coordinated action must be carried out between the State Attorney' s General Office and the Judiciary under the prism of the principles of procedural consistency and participation.